Determining the effect of stator groove geometry in a traction synchronous reluctance motor with permanent magnets on the saw-shaped electromagnetic moment level - Liubarskyi, Borys; Riabov, Ievgen; Iakunin, Dmytro; Dubinina, Oksana; Nikonov, Oleh; Domansky, Vasily (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports the model of a magnetic field of the synchronous reluctance motor with permanent magnets that was developed on the basis of a finite-element method. The model was implemented in the FEMM finite-element analysis programming environment involving the application of the Lua-based script. The model makes it possible to determine the dependence of the engine's electromagnetic moment on the rotor rotation angle. Determining the level of a saw-shaped moment is important for assessing its harmful effect on the structural elements of the traction motor and the drive in general. The results of digital modeling have established the dependences of the electromagnetic moment on the rotor rotation angle. The moment has a variable component – the saw-shaped moment, whose amplitude for open grooves under a rated load mode is 182 Nm, and for semi-open grooves ‒ 90 Nm. The use of semi-open grooves exerts a positive effect on eliminating the saw-shaped moment in a synchronous reluctance motor with permanent magnets and may be recommended for further application on engines of this type. Semi-open grooves reduce the opening of the stator groove by 2 times and lead to a smoother flux distribution under the gear division. That reduces the oscillations of the main magnetic flux. The proposed application of semi-open stator grooves makes it possible to reduce by more than 2 times the level of a saw-shaped moment of the synchronous reluctance motor with permanent magnets under a rated mode. It has been determined that a rather positive factor is an increase of 4.8 % in the average motor moment value under a rated mode when using semi-open grooves. This is due to a decrease in the average value of magnetic resistance to the main magnetic flux. Therefore, with a simultaneous decrease in the moment's fluctuations, the transition to semi-open grooves makes it possible to improve the mass-dimensional indicators of the motor in general.